THE RELATIONSHIP BETWEEN THE BIG FIVE PERSONALITY TYPES AND GPA AMONG MEDICAL STUDENTS FROM THE EAST INDONESIA SCHOOL OF MEDICINE - Pretty Mitra Kristina Zebua; Marliyati Sanaky; Farah Christina Noya (Universitas Gadjah Mada, 2026)
Background: GPA is a key indicator of academic success among students at the Faculty of Medicine, Pattimura University. Academic data from the 2022 cohort show an increase in students with GPAs below 2.50, which poses a risk of academic dismissal and may negatively impact institutional performance. Personality is one of the psychological factors believed to influence academic achievement, particularly through the five types of the Big Five Personality model: neuroticism, extraversion, openness, agreeableness, and conscientiousness.Objective: To examine the relationship between Big Five Personality types and GPA among medical students of the 2022 cohort at Pattimura University.Methods: This was an analytic observational study with a cross-sectional design conducted from May to June 2025. Total sampling was used, involving 187 respondents. Personality data were collected using the IPIP-BFM-50 questionnaire, while GPA data were obtained from academic records. Data analysis was performed using the Chi-square test and post-hoc test for individual types.Results: A significant relationship was found between the Big Five Personality types and GPA (p = 0.001). Specifically, neuroticism (p = 0.000) was significantly related to GPA, while conscientiousness, openness, extraversion, and agreeableness showed no significant relationship.Conclusion: Understanding students’ personality types can serve as a foundation for developing more personalized, adaptive, and effective learning strategies within medical education.